Dissociative recombination of (HeH+)-He-3: comparison of spectra obtained with 100, 10 and 1 meV temperature electron beams - Al-Khalili, A; Danared, H; Larsson, M; Le Padellec, A; Peverall, R; Rosen, S; Semaniak, J; af Ugglas, M; Vikor, L; van der Zande, P (1998)
The heavy-ion storage ring CRYRING at the Manne Siegbahn Laboratory at Stockholm University has been used for the study of dissociative recombination of 3HeH+. The new adiabatically expanded electron beam at CRYRING, which is achieved by means of a superconducting magnet, was used. The electron-beam expansion factor of 100 gave a transverse electron temperature of about 1 meV. This allowed the observation of several new resonances in the recombination cross-section.